P2_8 It’s the wrong trousers Gromit! Part 2 - Raymer, Katie; Jordan, Benjamin; Youle, Oliver; Morris, Thomas (Physics Special Topics, 2013)
Following on from a previous paper by Raymer et al. (2013) this paper considers whether the magnetic field generator in the boots of the ex-NASA Techno Trousers would work. It is found that the field generated needs to be 0.37T. A flat, cylindrical electromagnet with an iron core would be able to produce a field of this magnitude and hence the trousers would work.Â 